ESTIMATING THE SIZE OF FIRST MATURITY OF NILE TILAPIA (Oreochromis niloticus) IN SIDENRENG LAKE, SOUTH SULAWESI - Hasrianti Hasrianti; Damis Damis; Gondo Puspito; A Rini Sahni Putri; Wirata Wirata (Politeknik Kelautan dan Perikanan Sorong, 2026)
Sidenreng Lake is an important inland water body in South Sulawesi that supports local capture fisheries, particularly Nile tilapia (Oreochromis niloticus) fishing using gillnets. High fishing pressure and the use of various mesh sizes may result in the capture of fish before reaching sexual maturity. This study aimed to estimate the size at first maturity of Nile tilapia and evaluate the suitability of gillnet mesh sizes used by fishers in Sidenreng Lake. The study was conducted from August to October 2024 using gillnets with mesh sizes of 2”, 2.5”, 3”, and 3.5”, with 20 fishing trials. The observed parameters included fork length, body girth, body weight, gonad weight, gonad maturity stage, gonadosomatic index, size at first maturity, and size at first capture. The results showed that most of the observed Nile tilapia were at gonad maturity stages I and II, accounting for 69%, while mature fish at stages III and IV accounted for only 31%. The growth patterns of male and female Nile tilapia were negatively allometric, with b values of 2.90 and 2.88, respectively. The size at first capture of male Nile tilapia was 133.74 mm, while the size at first maturity was 196.20 mm. In females, the size at first capture was 124.09 mm, while the size at first maturity was 185.84 mm. The lower Lc values compared to Lm indicate that most Nile tilapia were caught before having the opportunity to reproduce. Therefore, the currently used gillnet mesh sizes are not yet selective, and mesh sizes larger than 3.5” are recommended to support the sustainability of Nile tilapia resources in Sidenreng Lake.